MCAM in Melanoma Metastasis: The Role of Putative Endocytosis Motifs - Harfield, Jake (Curtin University, 2021)
Melanoma cell adhesion molecule (MCAM) is a marker of melanoma metastasis and contributes to melanoma progression but how MCAM is sorted and recycled through the cell is unknown. Two putative endocytosis motifs have been identified in the intracellular domain of MCAM. The generation of wild-type and mutant MCAM expressing Colo239F cells was explored in this thesis to determine the role of these endocytosis motifs in melanoma metastasis.